IMPLIKASI KELUARNYA PERMEN KLHK P.68 TAHUN 2016 TENTANG BAKU MUTU LIMBAH DOMESTIK PADA PENEGAKAN HUKUM DI DKI JAKARTA DAN PEMILIHAN TEKNOLOGI PENGOLAHAN LIMBAH - Herlambang, Arie; said, nusa idaman (Center for Environmental Technology, 2016)
The existence of regulations to control environmental pollution has grown over time in line with changes in environmental legislation. In Indonesia since the '80s has been three times experience changes in environmental legislation. Any change in the law is always followed by changes in regulations that are below it. From time to time, the environmental pollution is getting worse and require stricter regulations and implementation. Regulations are too strict sometimes not implementable and eventually are violated because there is no way out solution that does not burden the parties. Domestic waste is the largest portion of urban waste. Its existence has made the environment of rivers, lakes and ground water polluted, due to not properly managed. Regulation of waste quality standards have been tightened over time. Waste water quality standard is the limit or polluted substance or the amount of pollutant elements are tolerable in the waste water to be discharged or released into the water source from a business or activity. The existence of environmental quality standards in Indonesia are set by regulations of environment ministers. Discharge of domestic waste quality standards number P.68 / Menlhk / Secretariat / Kum.1 / 8/2016 has brought on changes in the use of domestic wastewater treatment technologies, as happened tightening in several key parameters, which is still within the limits loose.Ã‚Â Keywords : Environmental regulation, waste treatment technology